Blood-brain barrier in drug discovery : optimizing brain exposure of CNS drugs and minimizing brain side effects for peripheral drugs - Di, Li; Kerns, Edward Harvel (Hoboken, New Jersey : John Wiley & Sons Inc., 2015)
'Focused on central nervous system (CNS) drug discovery efforts, this book educates drug researchers about the blood-brain barrier (BBB) so they can affect important improvements in one of the most significant - and most challenging - areas of drug discovery. Written by world experts to provide practical solutions to increase brain penetration or minimize CNS side-effects. Reviews state-of-the-art in silico, in vitro, and in vivo tools to assess brain penetration and advanced CNS drug delivery strategies. Covers BBB physiology, medicinal chemistry design principles, free drug hypothesis for the BBB, and transport mechanisms including passive diffusion, uptake/efflux transporters, and receptor-mediated processes. Highlights the advances in modelling BBB pharmacokinetics and dynamics relationships (PK/PD) and physiologically-based pharmacokinetics (PBPK). Discusses case studies of successful CNS and non-CNS drugs, lessons learned and paths to the market'--Provided by publisher.
1. Introduction and overview / Li Di (Pfizer Inc.), Edward H. Kerns -- Pharmacokinetics of Brain Exposure -- 2. Pharmacokinetics of CNS penetration / Andreas Reichel (Bayer) -- 3. Free Drug Hyposthesis for CNS Drug Candidates / Xingrong Liu (Genentech) -- 4. Species Differences and impact of desease state on BBB / Jean-Marie Nicolas (UCB Pharma S.A.) -- Mechanisms of Drugs Across the Blood-Brain Barrier -- 5. Passive diffusion permeability of the BBB -- examples and SAR / Phil Jeffrey (GSK) -- 6. Efflux transport at the BBB -- examples and SAR / Jerome Hochman (Merck) -- 7. Uptake transport at the BBB -- examples and SAR / Zack Cheng (AstraZeneca) -- 8. Uptake of proteins and antibodies at the BBB / William Pardridge (UCLA) -- Predicting and Measuring Brain Exposure of Drugs -- 9. In silico tools for assessing brain exposure / Hongming Chen (AstraZeneca) -- 10. In vitro assays for assessing BBB permeability -- vascular cells, artificial membranes, brain slice, cell uptake / Winfried Neuhaus (University of Vienna) -- 11. Human-based in vitro endothelial cell models / Eric Shusta (University of Wisconsin) -- 12. In vitro assays for assessing brain binding / Li Di (Pfizer) -- 13. In vivo studies of brain exposure / Edward H. Kerns -- 14. PBPK models for BBB / Elizabeth de Lange (Leiden University) -- 15. PK/PD modeling of CNS drug candidates / Johan Gabrielsson (Swedish University) -- 16. Microdialysis to assess free drug concentration in brain / William Kielbasa (Lilly) -- 17. Imaging technique for CNS drug discovery / Lei Zhang (Pfizer Inc.) -- Modulating Brain Penetration of Leads During Drug Discovery -- 18. Designing CNS drugs for optimal brain exposure / Zoran Rankovic (Lilly) -- 19. Case studies of CNS drug optimization -- medicinal chemistry and CNS biology perspectives / Kevin J. Hodgetts (Harvard NeuroDiscovery Center) -- 20. Designing peripheral drugs for minimal brain exposue / Peter Bungay (Pfizer) -- 21. Case studies of non-CNS drugs to minimize brain penetration -- Nonsedative antihistamines / Andrew Crowe (Curtin University) -- Case Studies in CNS Drug Discovery -- 22. Case study 1 on discovery of a successful CNS drug -- Fycompa (AMPA Receptor Antagonist) / Andrew Satlin and Antonio Laurenza (Eisai) -- 23. Case study 2 on discovery of a successful CNS drug -- Vortioxetine (Serotonin Modulator and Stimulator) / Benny Bang-Andersen (Lundbeck) -- Drug Delivery Techniques to CNS -- 24. Brain delivery using nanotechnology / Xinguo Jiang (Fudan University) -- 25. Intranasal delivery to CNS / Lisbeth Illum (University of Nottingham) -- Future Prospective in Blood Brain Barrier Advancement -- 26. Future perspectives / Joan Abbott (King's College).
Includes bibliographical references and index.
Keywords: Blood-brain barrier -- Metabolism; Central Nervous System Agents -- pharmacokinetics; Blood-Brain Barrier -- drug effects; Central nervous system diseases -- Drug therapy; Drug Discovery -- methods; Drug-Related Side Effects and Adverse Reactions -- prevention & control